Gestión Administrativa en la Hacienda Agrícola La Elba - Aucancela Pilco, Alex Dario (2018)
n most organizations there is some kind of problem, caused by human talent, material resources, technological, financial, or any other aspect. These problems are caused by different characters, such as: irresponsibility, lack of capacity, insufficient resources, etc., leading to consequences that at some point will cause serious repercussions for the organization. These problems usually arise at any stage of organizational development, either at the beginning of an activity or at the maturity stage, and for the La Elba agricultural farm it is not the exception.